Effect of Multiple-Nutrient Supplement on Muscle Damage, Liver, and Kidney Function After Exercising Under Heat: Based on a Pilot Study and a Randomised Controlled Trial - Wei, Chunbo; Zhao, Shengnan; Zhang, Yuntao; Gu, Wenbo; Kumar Sarker, Shuvan; Liu, Shuande; Li, Benzhang; Wang, Xuanyang; Li, Ying; Wang, Xu (Frontiers in Nutrition, 2021)
Objective: This study explored the effect of multiple-nutrient supplementation on muscle damage and liver and kidney function after vigorous exercise under heat. Methods: After an initial pilot trial comprising 89 male participants, 85 participants were recruited and assigned into three groups: a multiple-nutrient (M) group, a glucose (G) group and a water (W) group. Multiple-nutrient supplements contain glucose, fructose, maltose, sodium, potassium, vitamin B1, vitamin B2, vitamin C, vitamin K and taurine. Participants were organized to take a 3 km running test (wet-bulb globe temperature 32 °C) after a short-term (7 days) supplement. Blood samples were obtained to detect biochemical parameters (glucose (GLU), aspartate amino transferase (AST), alanine amino transferase (ALT), blood urea nitrogen (BUN), uric acid (UA), creatinine (Cr), creatine kinase (CK), lactate dehydrogenase (LDH)), lactic acid, inflammation factors (interleukin-6 (IL-6), tumour necrosis factor-α (TNF-α)) and oxidative stress biomarkers (superoxide dismutase (SOD), 8-iso-prostaglandin F (2alpha) (8-iso-PGF2α)). Results: In the pilot trial, BUN decreased significantly in the M and G groups immediately after the running test. AST, Cr and UA were significantly reduced 24 hours after the running test with single-shot multiple-nutrient supplementation. In the short-term trial, multiple nutrients further prevented the elevation of CK (p=0.045) and LDH (p=0.033) levels 24 hours after strenuous exercise. Moreover, we found that multiple nutrients significantly reduced IL-6 (p=0.001) and TNF-α (p=0.015) elevation immediately after exercise. Simultaneously, SOD elevation was significantly higher in the M group immediately after exercising than in the other two groups (p=0.033). 8-iso-PGF2α was reduced in the M Group 24 hours after exercise (p=0.036). Conclusions: This study found that multiple-nutrient supplementation promoted the recovery of muscle damage and decreased liver and kidney function caused by strenuous exercise in a hot environment, probably through the inhibition of secondary damage induced by increased inflammatory reactions and oxidative stress. In this respect, the current study has important implications for the strategy of nutritional support to accelerate recovery and potentially prevent heat-related illness. This study was prospectively registered on clinicaltrials.gov on June 21, 2019 (ID: ChiCTR1900023988).